Ab initio investigation of the ground and excited states of ZrO+ and NbO+. (November 2020) - Ariyarathna, Isuru R.; Miliordos, Evangelos
Highlights: We used high-level ab initio quantum calculations to study low-lying electronic states of ZrO+ and NbO+. We report electronic configurations, bond distances, potential energy curves, spectroscopic constants, spin–orbit splittings, and excitation energies of low-lying electronic states of ZrO+ and NbO+. Low-lying electronic states of ZrO+ and NbO+ possess M3+O2− oxo character. We rectify spectroscopic assignments made for ZrO+ and NbO+ in the literature. Abstract: High-level ab initio quantum calculations were performed to study thirteen and sixteen low-lying electronic states of ZrO + and NbO + . We report their potential energy curves, electronic configurations, bond distances, harmonic vibrational frequencies, anharmonicities, spin–orbit splittings, and excitation energies. Chemical bonding patterns for low-lying electronic states are also proposed. The removal of one electron from the 5sZr of ZrO creates the first three states of ZrO + (X 2 Δ, 1 2 Σ +, 1 2 Π). These three states bear oxo (Zr 3+ O 2− ) character and the remaining states show oxyl (Zr 2+ O · − ) nature. Similarly, the detachment of one electron from 5sNb of nine low-lying states of NbO generate the nine lowest energy states of NbO + that possess oxo (Nb 3+ O 2− ) character. Low-lying electronic states of ZrO + and NbO + are very similar to their isovalent TiO + and VO + partners. The current study rectifies spectroscopic assignments made for ZrO + and NbO + in the literature.